REPORT OF THE COMMITTEE ON COURSES AND CURRICULA–GENERAL. - Frank, Werner G.; Holmes, James D.J.; Scholsser, Robert E.; Woods, Richard S.; Bower, James B. (The Accounting Review, 1964)
The article presents information on the report of the Committee on Courses and curricula-General of American Accounting Association. The Committee's task, briefly, was to develop a comprehensive body of liberal arts and general business knowledge to include in an accounting major's college curriculum. The Committee believes that the development of a professional accountant should be viewed as an amalgam of formal and informal education in which college education plays only one important part. The prime objective of the accounting major's college education is not to train him for a specific job or even to train him for his chosen career, but rather to create a capacity within him for gradual development in the years which lie ahead as he faces the challenges of his profession. Thus, the development of abilities to reason, to communicate, to organize and act when confronted by various business situations become important considerations in structuring knowledge for an accounting curriculum. The conclusions reached in this report are obviously of a subjective nature rather than being based on empirical evidence. They may be colored by personal opinions and biases. Yet, these conclusions have run the gauntlet of approval by an eight-man committee constituted, as the reader may see, of a wide variety of experiences and interests.